PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PARTISIPASI STAKEHOLDERS TERHADAP EFISIENSI PENGELOLAAN DANA PENDIDIKAN (Studi Kasus di Sekolah Dasar Negeri Se-Kecamatan IV Nagari, Kabupaten Sijunjung) - Raudya Tuzzahra; Lili Wahyuni; Witra Maison (Bajang Institute, 2022)
This study aims to determine the Effect of Accountability on the Efficiency of Education Fund Management, the Effect of Transparency on the Efficiency of Education Fund Management and the Effect of Stakeholder Participation on the Efficiency of Education Fund Management, as well as the Effect of Accountability, Transparency and Participation of Stakeholders simultaneously on the Efficiency of Education Fund Management. This research was conducted at the State Elementary School (SD) in District IV Nagari, Kab. Sijunjung, namely 13 (thirteen) elementary schools. The data used are primary data, the sample technique used is the total sample by distributing questionnaires. The sample in this study was the entire population, namely the Principal, Treasurer, Administration, Chairman of the Committee and 1 (one) teacher representative. The results show that each variable of accountability, transparency and stakeholder participation has a significant effect on the efficiency of education fund management, then accountability, transparency and stakeholder participation have a simultaneous effect on the efficiency of education fund management.